N01 Cell Transplantation In Huntington's Disease. (17th September 2014) - Clinch, S; Rosser, A; Lelos, M; Busse, M
Abstract : Introduction: Cell transplantation is becoming a viable therapy for patients with Huntington's disease (HD). Studies using rodent models of HD have identified a need for extended behavioural training to allow the recipient to 'learn to use the graft'. Thus, after intra-striatal grafting of foetal tissue, striatally-dependent behaviours need to be re-established through targeted training. Aims: To determine the extent to which cell transplantation can alleviate a range of cognitive deficits in rodent models of HD, and to identify the optimal parameters for successful alleviation of deficits. To develop a functional motor assessment in HD patients, that sensitively capture improvements in motor function that manifest post-transplantation. Method: Rats will be pre-trained on a cognitive operant task that relies on the medial striatum. After receiving bilateral striatal lesions, a subset will be grafted with foetal ganglionic eminence. Thereafter, rats will be re-tested on the task at either 2 or 12 weeks post-graft to determine the optimal time to commence cognitive training. In HD patients, a range of motor tasks will be assessed to identify the items most sensitive to HD pathology. From this, a unique assessment tool will be developed that can sensitively measure improvements in motor function following cell transplantation. Results: Results from the rat models of HD will help us understand the extent to which intra-striatal grafts can support cognitive and motor deficits, as well as revealing the optimal parameters for efficient use of the therapeutic intervention. Studies from patients with HD will help us to monitor the impact of the cell transplantation therapy through the development of a sensitive motor assessment. Conclusion: Understanding the optimal parameters for efficient grafting and being able to sensitively monitor any improvement in function, due to graft integration, is critical to our development of cell replacement therapies and will help us move this treatment to clinical application.